(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the process of formation of father and mother roles from a psychological point of view. It highlights the biological, social and personal factors of parental identification, as well as the influence of family environment and cultural values. The study reveals the mechanisms of development of father and mother roles based on psychoanalytic, individual, humanistic and attachment theories. Also, the modern transformation of parenting roles and their impact on the psychological development of the child’s personality are scientifically analyzed.